Primary school teachers ‘attitudes towards the physical education and sport session and its relation to occupational pressures - charef, Silarbi; Benrabeh, Kheiredine; boumaza, mohamedlamine (sports creativity, 2025)
The objective of this study is to know the relationship between the attitudes of primary school teachers towards the session of physical education and sports and professional pressures. To achieve this, the researchers relied on the descriptive approach based on a questionnaire addressed to a sample of 100 teachers (male and female ) , we have used two questionnaires, the first for attitudes and the second for occupational pressures. After collecting data and the statistical analyses, we have found that there is a moderate level on the attitude of the teachers towards the session of PES and a high level for the professional pressures to found that there is close strong correlation between the attitudes of primary school teachers towards the physical education and sports session and the professional pressures